Returning home with glory : Chinese villagers around the pacific, 1849 to 1949 - Williams, Michael (Crossing Seas., 2018)
Employing the classic Chinese saying "returning home with glory" (man zai rong gui) as the title, Michael Williams highlights the importance of return and home in the history of the connections established and maintained between villagers in the Pearl River Delta and various Pacific ports from the time of the Californian and Australian gold rushes to the founding of the People's Republic of China. Conventional scholarship on Chinese migration tends to privilege nation-state factors or concepts which are dependent on national boundaries. Such approaches are more concerned with the migrants' set.